Numerical investigation of the effective mechanical properties and local stress distributions of TPMS-based and strut-based lattices for biomedical applications. (February 2022) - Chatzigeorgiou, Chrysoula; Piotrowski, Boris; Chemisky, Yves; Laheurte, Pascal; Meraghni, Fodil
Abstract: Porous structures, including those with lattice geometries, have been shown to mimic the mechanical properties of the human bone. Apart from the widely known strut-based lattices, the Triply Periodic Minimal Surfaces (TPMS) concept has been introduced recently to create surface-based lattices and to tailor their mechanical behaviors. In this study, the numerical investigation of the effective elastic properties, the anisotropic behavior, and the local stress distributions of a broad range of topologies provide us with a complete numerical tool to assist bone implant design. The comparison database of the lattices includes TPMS-based lattices, both sheet, and skeletal, as well as strut-based lattices. The lattices are subjected to periodic boundary conditions and also, a homogenization method is deployed to simulate the response of the lattice unit cells determining their apparent equivalent stiffness. A correlation among the lattice topologies, their effective mechanical properties, and the local Von Mises stress concentrations in them is observed. The stress distribution of various topologies with the same elastic modulus is examined to combine all the investigations. Finally, a large variety of numerical results are presented to allow the comparison of the lattice structures and the selection of the optimal configuration that mimics the elastic properties of the bone. Graphical abstract: Image 1 Highlights: A broad database of Triply Periodic Minimal Surfaces-based unit cells is generated. Periodic boundary conditions and a homogenization method are applied. The effective mechanical and anisotropic properties of the unit cells are computed. Investigation and statistical comparison of the local stress distributions in lattices. Unit cell topologies with iso-density and/or iso-effective elastic modulus.